Morphometric relationships and their contribution to biomass and cannabinoid yield in hybrids of hemp (Cannabis sativa). (21st July 2021) - Carlson, Craig H; Stack, George M; Jiang, Yu; Taşkıran, Bircan; Cala, Ali R; Toth, Jacob A; Philippe, Glenn; Rose, Jocelyn K C; Smart, Christine D; Smart, Lawrence B
Abstract : Stem and canopy architecture traits are superior predictors of floral biomass yield and offer a good indication of hybrid uniformity in field plantings of genetically diverse cannabinoid hemp populations. Abstract: The breeding of hybrid cultivars of hemp ( Cannabis sativa L.) is not well described, especially the segregation and inheritance of traits that are important for yield. A total of 23 families were produced from genetically diverse parents to investigate the inheritance of morphological traits and their association with biomass accumulation and cannabinoid yield. In addition, a novel classification method for canopy architecture was developed. The strong linear relationship between wet and dry biomass provided an accurate estimate of final dry stripped floral biomass. Of all field and aerial measurements, basal stem diameter was determined to be the single best selection criterion for final dry stripped floral biomass yield. Along with stem diameter, canopy architecture and stem growth predictors described the majority of the explainable variation of biomass yield. Within-family variance for morphological and cannabinoid measurements reflected the heterozygosity of the parents. While selfed populations suffered from inbreeding depression, hybrid development in hemp will require at least one inbred parent to achieve uniform growth and biomass yield. Nevertheless, floral phenology remains a confounding factor in selection because of its underlying influence on biomass production, highlighting the need to understand the genetic basis for flowering time in the breeding of uniform cultivars.